OBSERVATIONS ON THE LOBSTERS OF MINICOY ATOLL - Pillai, C S Gopinatha; Mohan, Madan; Kunhikoya, K K (Indian Journal of Fisheries, 2011)
The rock-lobsters Panulirus penicillatus, P. homariis and P. versicoloroccur in Minicoy. P. versicolor, now the most common, is possibly a recentarrival as this species has not been previously recorded from here. The spatialdistribution, social behaviour, local migration on the reef flats, specific habitatselection and juvenile recruitment of the species in the atoll are discussed.